GROUNDWATER LEVEL INFLUENCE ON SELECTED SOIL AND GROUNDWATER PHYSICOCHEMICAL PROPERTIES IN AN OIL PALM PLANTATION - Anggat, F.; Sangok, F. E.; Busman, N. A.; Melling, L.; Lim, Soh Fong; Mah, Yau Seng (2023)
Groundwater management such as drainage are required in agricultural land for crop cultivation, which removes excess water from within the soil by lowering the groundwater level (GWL) (Hillel, 2007). Drainage is required to facilitate respiration of plant roots in peatland for agricultural use, regulates water regime in soil-water system and maintain available soil moisture content (Miyamoto et al., 2009; Blasko, 2011). Drainage also influences soil material transport and leaching process, vegetation structure, soil organic carbon and total nitrogen (Blasko, 2011; Mansouri et al., 2020; Guan et al., 2021). GWL could increase nutrients concentration in groundwater due to agriculture related activities such as fertilizer application and irrigation flow (Rajmohan and Elango, 2005). In agricultural activities such as oil palm cultivation, soil has undergone drainage, which is a pre-requisite for oil palm plantation activities (Sangok et al., 2017). Despite that, studies on the effect of GWL on soil and groundwater physicochemical characteristics under oil palm plantation is still limited. To ensure more sustainable oil palm cultivation, it is important to understand the impacts of GWL on soil physicochemical parameters such as hydrogen potential (pH), soil moisture and bulk density, and on groundwater nutrients such as K+ and NO3- and the relationship between them. Thus, in this study, we evaluate the effect of different GWL on the selected tropical peat soil and groundwater physicochemical properties in an oil palm plantation with comparison to a drained secondary forest.